PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 LENGAYANG TAHUN PELAJARAN 2012/2013 - Marici, Fitrina; Husna, Husna; Cesaria, Anna (Pendidikan Matematika, 2013)
This research is background by the studentsâ understanding of mathematics concepts still low and a small portion of students can not sit still for more than two minutes in the learning process. This study aims to determine whether studentsâ understanding of mathematics concepts by applying techniques Quick On The Draw is better than the studentsâ understanding of concepts mathematics by applying conventional learning class VII SMP N 1 Lengayang. This is experimental with randomized trials on the subject. The population in this study were all enrolled students of class VII in the school year 2012/2013. Samples were VII6 class as the experimental class and the control class VII7 class. The research instrument is the ultimate test with reliability = 0,79. Based on the analysis of the data found that the samples are normally distributed and homogeneous on the real level Î± = 0,05. Test results hypothesis by t test using MINITAB software obtained P-value = 0,032 is less than Î± = 0,05. So it can be concluded that the studentsâ understanding of mathematics concepts by using the Quick On The Draw Technique is better than the studentsâ understanding of mathematics concepts by using conventional learning in class VII SMP N 1 Lengayang at 95% confidence level.